Finance, investment, and firm value in Germany and the US: A comparative analysis - Eric Nowak (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Germany and the United States are generally seen as the two competing systems of corporate governance. In search for a comparative welfare analysis of the financial systems, we are interested in (i) the aggregate value-added of corporate investments in the two countries and in (ii) the interaction of investment and financing decisions. This paper investigates the impact of financing, investment, and dividend decisions on the value of stock corporations in Germany and the US. The methodology is based on a cross-sectional approach proposed by Fama and French. In general, the evidence shows that relations for the German firms are statistically similar to those found for their US counterparts. In both countries, corporate investment creates value in excess of cost, but the US industrial sector seems to be more efficient in making value-enhancing investments. Robust statistical methods are applied to verify the results. They do not change the main conclusions.
urn:nbn:de:kobv:11-10057024
Keywords: 330